STAT3-Mediated Metabolic Reprograming in Cellular Transformation and Implications for Drug Resistance - Poli, Valeria; Camporeale, Annalisa (Frontiers in Oncology, 2015)
Signal Transducer and Activator of Transcription (STAT)3 mediates the signaling downstream of cytokine and growth factor receptors, regulating the expression of target genes. It is constitutively phosphorylated on tyrosine (Y-P) in many tumours, where its transcriptional activity can induce a metabolic switch towards aerobic glycolysis and down-regulate mitochondrial activity, a prominent metabolic feature of most cancer cells, correlating with reduced production of ROS, delayed senescence and protection from apoptosis. STAT3 can however also localize to mitochondria, where its serine-phosphorylated (S-P) form preserves mitochondrial oxidative phosphorylation and controls the opening of the mitochondrial permeability transition pore, also promoting survival and resistance to apoptosis in response to specific signals/oncogenes such as RAS. Thus, downstream of different signals, both nuclear, Y-P STAT3 and mitochondrial, S-P STAT3 can act by promoting cell survival and reducing ROS production. Here, we discuss these properties in the light of potential connections between STAT3-driven alterations of mitochondrial metabolism and the development of drug resistance in cancer patients.